Comparison of Serum Vitamin D Levels in Preeclamptic and Normotensive Pregnant Women: A Case-Control Study - Manzoor, Mahrukh; Majid, Erum; Komal, .; Sultan, Kainat; Sadia, .; Ali, Sidra (Biological and Clinical Sciences Research Journal, 2025)
Preeclampsia remains a significant cause of maternal and perinatal morbidity and mortality worldwide. Vitamin D deficiency has been implicated in adverse pregnancy outcomes, but its role in the development of preeclampsia is still under investigation. Objective: To compare serum vitamin D levels in preeclamptic and normotensive pregnant women and evaluate the possible association between vitamin D deficiency and preeclampsia. Case-control study. Place and Duration of Study: Department of Obstetrics and Gynaecology, Jinnah Postgraduate Medical Centre (JPMC), Karachi, Methodology: A total of 114 pregnant women aged 18–40 years with a gestational age of 20–40 weeks were enrolled using a non-probability consecutive sampling technique. Participants were divided into two groups: 57 preeclamptic women (cases) and 57 normotensive pregnant women (controls). Preeclampsia was defined as blood pressure ≥140/90 mmHg on two separate occasions, four hours apart, along with proteinuria ≥+1 on dipstick or >300 mg in 24 24-hour urine collection. Women with chronic hypertension, diabetes, renal disease, autoimmune conditions, or a prior history of preeclampsia were excluded. Demographic variables, including parity, were recorded for all participants. Serum 25-hydroxyvitamin D [25(OH)D] levels were measured using a standardized chemiluminescent immunoassay. Data were analyzed using SPSS version 20. Independent t-tests and Chi-square tests were applied, with a p-value < 0.05 considered statistically significant. Results: The mean age of participants was 28.6 ± 4.9 years in the preeclamptic group and 27.9 ± 5.2 years in the normotensive group. Most women were multigravida (62.3%) and in the third trimester (68.4%). The mean serum vitamin D level was significantly lower in the preeclamptic group (13.45 ± 4.86 ng/ml) compared to the normotensive group (19.22 ± 5.02 ng/ml, p < 0.001). Vitamin D deficiency (<30 ng/ml) was observed in 53/57 (93.0%) preeclamptic women compared to 44/57 (77.2%) normotensive women (p = 0.02). Stratified analysis further confirmed that the association between vitamin D deficiency and preeclampsia persisted across different age, parity, and gestational age categories. Conclusion: Vitamin D deficiency shows a significant association with preeclampsia, with affected women having substantially lower serum vitamin D levels compared to normotensive pregnant women. Routine screening and timely supplementation of vitamin D during pregnancy may help reduce the risk of preeclampsia and improve maternal outcomes.